Old Testament days : an activity guide - Sanders, Nancy I. (Chicago, Ill. : Chicago Review Press, 1952)
Uses more than eighty activities and projects to provide insight into life in the Middle East during the period covered by the Old Testament.
Includes bibliographical references (p. 166).
Keywords: Bible -- Antiquities -- Juvenile literature; Bible -- Antiquities; Palestine -- Social life and customs -- Juvenile literature; Middle East -- Civilization -- To 622.